Review: Millenia of Language Change. Sociolinguistic Studies in Deep Historical Linguistics - Rogos-Hebda, Anna (Studia Anglica Posnaniensia, 2020)
Review: Millenia of Language Change. Sociolinguistic Studies in Deep Historical Linguistics